International consensus statement on the peri‐operative management of direct oral anticoagulants in cardiac surgery1. (27th September 2018) - Erdoes, G.; Martinez Lopez De Arroyabe, B.; Bolliger, D.; Ahmed, A. B.; Koster, A.; Agarwal, S.; Boer, C.; von Heymann, C.
Summary: Despite current recommendations on the management of severe peri‐operative bleeding, there is no pragmatic guidance for the peri‐operative monitoring and management of cardiac surgical patients taking direct oral anticoagulants. Members of the Transfusion and Haemostasis Subcommittee of the European Association of Cardiothoracic Anaesthesiology, of their own volition, performed an independent systematic review of peer‐reviewed original research, review articles and case reports and developed the following consensus statement. This has been endorsed by the European Association of Cardiothoracic Anaesthesiology. In our opinion, most patients on direct oral anticoagulant therapy presenting for elective cardiac surgery can be safely managed in the peri‐operative period if the following conditions are fulfilled: direct oral anticoagulants have been discontinued two days before cardiac surgery, corresponding to five elimination half‐live periods; in patients with renal or hepatic impairment or a high risk of bleeding, a pre‐operative plasma level of direct oral anticoagulants has been determined and found to be below 30 ng.ml −1 (currently only valid for dabigatran, rivaroxaban and apixaban). In cases where plasma level monitoring is not possible (e.g. assay was not available), discontinuation for 10 elimination half‐live periods (four days) is required. For FXa inhibitors, a standard heparin‐calibrated anti‐Xa level of < 0.1 IU.ml −1 should be measured, indicating sufficient reduction in the anticoagulant effect. Finally, short‐term bridging with heparin is not required in the pre‐operative period.